Foreign direct investment (FDI) flows to developing economies: Malaysia / Norashikin Zulkifli - Zulkifli, Norashikin (Faculty of Business Management, 2014)
Foreign direct investment (FDI) is playing an important role as external financing of developing and developed countries. Including Malaysia, foreign direct investment is one of the sources of country income. Statistically has shown that foreign direct investment in Malaysia show a fluctuation decreasing and increasing every year. When the foreign direct investment is not consistently increasing, it may cause a problem to government. The government needs funds to implement Malaysia‟s Economic Transformation Program to achieve 2020 mission. However, it might be stagnated as there is a deficit in income. Therefore, the studies regarding the factor determine foreign direct investment in Malaysia is needed. Thus, this paper aims at finding out the relationship between macroeconomic variables which is market size, trade openness and exchange rate towards foreign direct investment (FDI). The results of this research paper would provide with an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively. This research paper concentrate on secondary data collected from World Data Bank comprises of 33 observations from 1980 to 2013. Multiple linear regressions with time series data were use to investigate the relationship of independent and dependent variables. The result is expected that all variables are significant to foreign direct investment.